669. Rapid Molecular Testing of Sputum for Identification of Pulmonary Tuberculosis: Impact on Duration of Respiratory Isolation. (31st December 2020) - Acosta, Tommy J Parraga; Vahia, Amit T; Hanna, Zachary W; Nair, Sashi N; Tibbetts, Robert; Alangaden, George J; Samuel, Linoj
Abstract: Background: Current guidelines recommend molecular testing directly on sputum of patients with suspected pulmonary tuberculosis (TB) to facilitate discontinuation of airborne infection isolation (AII). Henry Ford Hospital (HFH), a tertiary care center in Detroit, MI serves a population at high-risk for TB. Molecular testing of sputum using GeneXpert/MTB RIF (Xpert; Cepheid) (GXTB) was implemented at HFH on March 2019. Providers were permitted to remove patients from AII using 3 negative acid-fast bacillus smears (AFB) or 2 negative GXTB results. We evaluated the impact of GXTB on duration of AII over a 2-year period: Pre-implementation (January 2018 to February 2019) and post-implementation (March 2019 to February 2020). Methods: Retrospective data was abstracted for all patients placed in AII during the study period. Demographic data, TB risk factors, duration of AII, length of hospital stay (LOS), accuracy and turn-around-times (TAT) of AFB and GXTB were compared in the pre- and post-implementation periods. Categorical variables were studied using chi-square testing, and continuous variables were studied using T-test or Mann Whitney U test as appropriate. Results: During the study period, 269 patients with suspected TB were placed in AII: 137 pre-implementation and 132 post-implementation. Clinical characteristics and TB risk factors were generally comparable in both groups (Table 1). Abnormal chest X-ray was more frequent in patients in the post-implementation phase. All cases of culture positive TB were detected by AFB and GXTB. TAT of AFB results before and after implementation were similar and ranged from 20-24 hours (Table 2). In the post-implementation period, TAT of GXTB compared to AFB was 6.35 vs 21.28 hours (p < 0.0001). Duration of AII was shortened by almost 24 hours (70.2 vs 93.7 hours, p=0.031) (Table 3). Time from first sample collection to final results of all samples was 19.2 vs 52.6 hours, p< 0.0001. There was no difference in total LOS pre and post-implementation. Table 1. Clinical Characteristics of Patients with Suspected Pulmonary Tuberculosis Table 2. Turnaround times (TAT) of AFB and GeneXpert/MTB (Xpert) RIF before and after implementation Table 3. Duration of Airborne Isolation, Total Turn-Around Times, and Hospital Length of Stay in the Pre- and Post-implementation Period Conclusion: Implementation of rapid direct molecular testing reduced the duration of respiratory isolation for patients with suspected pulmonary TB. Further provider education regarding the reliability of GXTB in excluding TB may be necessary to reduce overall hospital LOS. Disclosures: All Authors : No reported disclosures